Persepsi Masyarakat Terhadap Kelompok Waria Pesantren - Vicktor Fadi; Suzy S. Azeharie (Koneksi, 2020)
Tranvestites as one part of the Lesbian, Gay, Bisexual, Transgender (LGBT) can be categorized as a muted group. They get discrimination and rejection in their activities. When they wanted to pray they were rejected by society. There is a group of transvestites who took the initiative to establish a pesantren in Yogyakarta that allows transvestites to do their spiritual activities. This research wants to know the perception of village people to the transvestites group in Yogyakarta. The purpose of this study is to find out the perception of village people to the transvestites group in pesantren Yogyakarta. The theories used in this study are the theory of communication and culture, perception and factors of the forming perception, muted group, transvestites and Javanese Islamic culture. The study uses phenomenology methods and features a descriptive approach. Research data is obtained from depth interviews on nine interviewees, observations, document studies and literature studies. The conclusion of this research is the perception of village people to the transvestites group of pesantren tends to be negative perception. The women villagers felt disturbed because there were members of the transvestites group who joined the women section while praying in the mosque. And this made the village people uncomfortable with the existence of a group of transvestites in the villages. The village people believe a concept that in the  world there are only men and women, while the concept of transvestites is still gray in society. Waria merupakan bagian dari Lesbian, Gay, Bisexual, Transgender (LGBT) dan termasuk dalam kategori kelompok bungkam. Waria kerap mendapat diskriminasi dan penolakan dalam melakukan kegiatan termasuk ketika ingin beribadah. Namun, terdapat kelompok waria yang berinisiatif mendirikan pesantren yang menampung waria agar dapat menjalankan aktivitas spiritual seperti masyarakat pada umumnya. Penelitian ini ingin mengetahui persepsi masyarakat kampung di Yogyakarta terhadap kelompok waria yang beribadah di pesantren. Tujuan penelitian ini adalah untuk mengetahui persepsi masyarakat kampung terhadap kelompok waria di pesantren. Teori yang digunakan dalam penelitian ini adalah teori komunikasi dan budaya, persepsi dan faktor-faktor pembentuk persepsi, kelompok bungkam, waria dan budaya Islam Jawa. Penelitian ini menggunakan metode fenomenologi dan dilengkapi pendekatan deskriptif. Data penelitian diperoleh dari wawancara terhadap sembilan narasumber, pengamatan, studi dokumen dan studi kepustakaan. Kesimpulan penelitian ini adalah persepsi masyarakat kampung terhadap kelompok waria pesantren cenderung negatif. Warga kampung yang merupakan perempuan merasa risih dengan adanya waria yang bergabung di bagian perempuan saat beribadah di masjid. Kondisi ini membuat masyarakat kampung tidak nyaman dengan keberadaan kelompok waria di kampung tersebut. Masyarakat kampung mempercayai konsep yang bahwa di dunia hanya terdapat laki-laki dan perempuan, sedangkan konsep waria masih abu-abu di masyarakat luas.